Extrapelvic Endometriosis Involving Pudendal and Sciatic Nerve Causing Obturator Muscle Atrophy - Ottavia Battaglia; Tjalina Hamerlynck; Pieter De Visschere (Journal of the Belgian Society of Radiology, 2024)
Teaching point: Extrapelvic endometriosis involving pudendal and sciatic nerve may be a cause of lower limb pain.